ANALYSIS OF PREPOSITION OF POSITION IN NARRATIVE TEXT AT SECOND GRADE STUDENTS OF MAN PASIR PENGARAIAN KABUPATEN ROKAN HULU - YANTI, RISNA; Sukma, Dian; Sukma, Dian; Rahayu, Pipit; Rahayu, Pipit (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research to know the skill of the second grade students of MAN Pasir Pengaraian in using preposition of position in narrative text. The participant of this research were second grade students of MAN Pasir Pengaraian Kabupaten Rokan Hulu. It has 4 classes, IPA and IPS. IPA there were two classes, consisted of 52 students and IPS there were two calsess, consisted of 50 students. Sample of this research was a kind of ârandom samplingâ and it had been taken 81 students as the sample. The research was a kind of descriptive qualitative research, the kind of this reseach had purpose to describe about the accurate situation. This research was done with some steps collected the data, analyzed the data, made conclusion, and report.Based on the analyzed the data which get by researcher, that skill of second grade students of MAN Pasir Pengarian was Poor category and its frequency were 76 % of the students. Good category so the percentage 6 %. Fairly Good level with the percentage 9 %. Then, Fair level with the percentage were 9%. So, it can be concluded that the students of second grade still in Poor level in using preposition of position in narrative text.